Carl Sandburg - Sandburg, Carl 1878-1967.; Schoonmaker, Frances 1941-.; Arcella, Steve (New York Sterling Pub., 1995)
Presents a collection of poems by the beloved American author who, as a young man, travelled across the Midwest as a hobo.
"A Magnolia Editions book"--T.p. verso.
Keywords: Children's poetry, American; American poetry